A Periodic Problem of a Semilinear Pseudoparabolic Equation - Yang Cao; Jingxue Yin; Chunhua Jin (Abstract and Applied Analysis)
A class of periodic problems of pseudoparabolic type equations with nonlinear periodic sources are investigated. A rather complete classification of the exponent p is given, in terms of the existence and nonexistence of nontrivial and nonnegative periodic solutions.